2022
DOI: 10.34172/jcs.2023.31790
|View full text |Cite
|
Sign up to set email alerts
|

The Conflict between the Beliefs of the Health Care Providers and Family Caregivers in the Use of Traditional Medicine in Pediatric Oncology: An Ethnographic Study

Abstract: Introduction: Traditional medicine are popular treatments among families of children with cancer. This study was designed to identify the behaviors, beliefs, and values of families and health care providers for the use of traditional medicine in pediatric oncology. Methods: This study was conducted with a focus on ethnography approach in the oncology department of a pediatric subspecialty hospital in northeastern of Iran from September 2021 to June 2022. A total of 20 key informants were observed and interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…The health-belief model of care among parents and guardians of children with cancer often includes decision-making based on personal experience with CAM, religious beliefs and recommendations from family members and friends [ 118 ]. In contrast, health-belief models of care among HCPs are invariably oriented first and foremost to evidence-based research and published clinical guidelines [ 119 ]. A qualitative study from the U.S. found that many pediatric oncologists report a need to “negotiate” with parents about CAM use, addressing issues such as delaying or refusing anti-cancer treatment; non-adherence to conventional treatment regimens; or even stopping treatment altogether [ 120 ].…”
Section: Methodsmentioning
confidence: 99%
“…The health-belief model of care among parents and guardians of children with cancer often includes decision-making based on personal experience with CAM, religious beliefs and recommendations from family members and friends [ 118 ]. In contrast, health-belief models of care among HCPs are invariably oriented first and foremost to evidence-based research and published clinical guidelines [ 119 ]. A qualitative study from the U.S. found that many pediatric oncologists report a need to “negotiate” with parents about CAM use, addressing issues such as delaying or refusing anti-cancer treatment; non-adherence to conventional treatment regimens; or even stopping treatment altogether [ 120 ].…”
Section: Methodsmentioning
confidence: 99%